On the linkage between tropospheric and Polar Stratospheric clouds in the Arctic as observed by space–borne lidar - Achtert, P.; Karlsson Andersson, M.; Khosrawi, F.; Gumbel, J. (Atmospheric Chemistry and Physics, 2012)
The type of Polar stratospheric clouds (PSCs) as well as their temporal and spatial extent are important for the occurrence of heterogeneous reactions in the polar stratosphere. The formation of PSCs depends strongly on temperature. However, the mechanisms of the formation of solid PSCs are still poorly understood. Recent satellite studies of Antarctic PSCs have shown that their formation can be associated with deep-tropospheric clouds which have the ability to cool the lower stratosphere radiatively and/or adiabatically. In the present study, lidar measurements aboard the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite were used to investigate whether the formation of Arctic PSCs can be associated with deep-tropospheric clouds as well. Deep-tropospheric cloud systems have a vertical extent of more than 6.5 km with a cloud top height above 7 km altitude. PSCs observed by CALIPSO during the Arctic winter 2007/2008 were classified according to their type (STS, NAT, or ice) and to the kind of underlying tropospheric clouds. Our analysis reveals that 172 out of 211 observed PSCs occurred in connection with tropospheric clouds. 72% of these 172 observed PSCs occurred above deep-tropospheric clouds. We also find that the type of PSC seems to be connected to the characteristics of the underlying tropospheric cloud system. During the Arctic winter 2007/2008 PSCs consisting of ice were mainly observed in connection with deep-tropospheric cloud systems while no ice PSC was detected above cirrus. Furthermore, we find no correlation between the occurrence of PSCs and the top temperature of tropospheric clouds. Thus, our findings suggest that Arctic PSC formation is connected to adiabatice cooling, i.e. dynamic effects rather than radiative cooling.